Hydrological regime of the transboundary Uldza River and terminal Torey Lakes under conditions of anthropogenic impact - M. A. Kashnitskaya; M. V. Bolgov (Юг России: экология, развитие, 2022)
Aim. Assess the change in the hydrological regime of the Torey Lakes based on a probabilistic forecast of the parameters of the water balance of these reservoirs, taking into account anthropogenic influence.Material and Methods. The study used materials from the state observation network of Roshydromet, Earth remote sensing data, research materials from scientific organisations and other sources of information that are in the public domain. Methods of statistical data analysis, mathematical modeling, hydrological calculations, including the water balance method and methods of processing and decoding satellite information were used.Results. With the implementation of the planned water management project, accompanied by additional non‐returnable water consumption in Mongolia, the consequences for the water regime of the Torey Lakes can be significant, especially in the low‐water phase of the water cycle, when the level decrease in the Barun‐Torey Lake will average 70 cm and in Zun‐ Torey – 80 cm. Through this project, the faster drying of the lakes, on average 2–3 years earlier, will be avoided.Conclusions. The ecological systems of the Dauria region are characterized by a process of cyclic succession and are mainly adapted to the contemporary climatic moisture cycle. For these ecosystems, any changes in external factors are fundamentally important, since they can lead to the irreversibility of natural processes. Based on the results obtained in this study, it is possible to conduct a comprehensive analysis of the anthropogenic impact on the state of the Torey Lakes and nearby ecosystems.